Commissural nucleus of the solitary tract lesions reduce food intake and body weight gain in rats - Menani, José Vanderlei [UNESP]; Colombari, Eduardo [UNESP]; Talman, William T.; Johnson, Alan Kim (Elsevier, 1996)
This study investigated the effects of an electrolytic lesion of the commissural subnucleus of the nucleus of the solitary tract (commNTS) on bodyweight, daily food and water intake, and plasma glucose and insulin in rats. In the first 6 days following brain surgery, commNTS lesioned rats reduced daily food intake by 80% compared to rats with sham lesions. After this period rats with lesions of commNTS started recovering food intake, but intake remained significantly reduced until the 12th day after surgery. A reduction in body weight was observed 4 days after surgery and reached a maximum on the 12th day. After this, a partial recovery of body weight was observed, but weight remained significantly reduced compared to weights of rats with sham lesions through the conclusion of the study. Food intake and body weight gain in other rats with partial lesions of the commNTS or with lesions outside the commNTS did not differ from rats with sham lesions with regard to those variables. Daily water intake and plasma glucose and insulin were not changed by the commNTS lesions. These results suggest that commNTS is involved with mechanisms that control food intake and body weight in rats.
Keywords: food ingestion; glucose; hindbrain; insulin; satiety; water intake; animal experiment; animal tissue; body weight; brain injury; controlled study; fluid intake; food intake; histology; priority journal; solitary tract nucleus; Non-programmatic; Body Weight; Drinking; Eating; Rats; Rats, Sprague-Dawley; Solitary Nucleus